A experimentação no ensino de Física: proposta de aplicação para temas do ensino médio - Costa, Farley William da (2017)
This work approaches theoretical topics of physics addressed to high school, which don’t usually appear in the literature of physics teaching but cause questions and curiosity in the students. This work used experimental techniques with everyday instruments. The topics covered were: the Circular Movement for First Year classes; study of Lenses and Vision for the second year, and the Electrical Circuits, series and parallel for the third year. The first and third year classes belong to a public school and the second year class in a private school, both at the city of Campinas. The experiments had the goal of using materials from the students' daily life, allowing a simple and low cost construction through donations and obsolete objects. This work also aims at the easy access to experimentation and to integrate theory to practice of the topics addressed in classes. In this way, it allows the experimentation as a catalyst or a facilitator of the learning, through motivation, the trial and error method, and by approximating the daily educational system to the scholar, in order to lead the student to build a meaningful learning. The data from the Physics teaching extent were collected using the qualitative research through questionnaires and testimonials from the students, which demonstrate the acceptance and the beginning of learning by them. The construction of the educational product takes into account several items: a lesson script, theoretical contributions to be developed and the experiments carried out with the students.